Feasibility of Conducting Autism Biomarker Research in the Clinical Setting. Issue 7 (September 2017) - Sices, Laura; Pawlowski, Katherine; Farfel, Laura; Phillips, Deirdre; Howe, Yamini; Cochran, David M.; Choueiri, Roula; Forbes, Peter W.; Brewster, Stephanie J.; Frazier, Jean A.; Neumeyer, Ann; Bridgemohan, Carolyn
ABSTRACT: Objective: Recruitment and completion of research activities during regular clinical care has the potential to increase research participation in complex neurodevelopmental disorders. We evaluated the feasibility, and effect on clinical care, of conducting biomarker research within a subspecialty clinical visit for autism spectrum disorder (ASD). Methods: Children, aged 5 to 10 years, were recruited by providers in ASD clinics at 5 institutions. Biomarkers collected were growth measurements, head circumference, neurologic and dysmorphology examinations, digit ratio (2D:4D) measurement, and platelet serotonin and urinary melatonin sulfate excretion levels. Parents completed the Aberrant Behavior Checklist—Community and a medical/demographic questionnaire. Cognitive level was abstracted from the medical record. Parents and clinicians completed surveys on the effect of the study on the clinical visit. Results: Eighty-three children and their caregivers participated. Factors limiting participation included difficulty reaching families by phone and parent concern about the study blood draw requirement. All children completed at least 4 of 7 planned research activities. Demographic factors, educational placement, and child behavior were not associated with completion of study activities. Lower nonverbal cognitive function was weakly associated with fewer activities completed. Forty-four percent of clinicians reported an effect of the research study on the clinical visit. However, neither parent-reported nor clinician-reported effect was associated with the degree of study activity completion. Conclusion: Recruiting study participants in the context of scheduled ASD clinical visits required significant effort. However, once recruited, participants completed most study activities, regardless of behavioral symptom severity. Research activities did not adversely affect the clinical visit.